2019
DOI: 10.1002/mnfr.201900044
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cocoa Prevents Aortic Remodeling and Vascular Oxidative Stress in Diabetic Rats

Abstract: Scope:The aim of the present study is to investigate the potential protective effect of a cocoa-rich diet on functional and structural vascular alterations in diabetes and the mechanism involved. Methods and results: Male Zucker diabetic fatty (ZDF) rats are fed on a standard (ZDF-C) or cocoa-rich diet (ZDF-Co) from week 10 to 20 of life. Diabetic ZDF-C rats showed increased blood pressure and enhanced aortic stiffness, as demonstrated by the increased pulse pressure and the augmented aortic medial thickness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…These results are consistent with several current studies evidencing the ability of certain flavonoids to prevent cardiac oxidative stress through the activation of Nrf2 and the consequent induction of antioxidant enzymes [ 40 , 41 , 42 , 43 ]. In particular, we recently found that supplementation with a cocoa rich diet prevented arterial oxidative damage by increasing the levels of Nrf2 and its antioxidant enzymes in the arteries of ZDF diabetic animals [ 19 ]. Collectively, these data indicate that CCB may alleviate myocardial fibrosis and the development of DCM in part by increasing Nrf2 levels and reducing oxidative stress in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with several current studies evidencing the ability of certain flavonoids to prevent cardiac oxidative stress through the activation of Nrf2 and the consequent induction of antioxidant enzymes [ 40 , 41 , 42 , 43 ]. In particular, we recently found that supplementation with a cocoa rich diet prevented arterial oxidative damage by increasing the levels of Nrf2 and its antioxidant enzymes in the arteries of ZDF diabetic animals [ 19 ]. Collectively, these data indicate that CCB may alleviate myocardial fibrosis and the development of DCM in part by increasing Nrf2 levels and reducing oxidative stress in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…ROS were quantified by the dichlorofluorescein (DCFH) assay based on the oxidation of dichlorofluorescein (DCF) that emits fluorescence [ 19 ]. LV homogenates were diluted with ice-cold Locke’s buffer (154 mM NaCl, 5.6 mM, KCl, 3.6 mM NaHCO 3 , 2 mM CaCl 2 , 10 mM D-glucose and 5 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfocnic acid, pH 7.4) and incubated with 5 μM DCFH for 30 min at 37 °C in darkness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, cocoa constitutes one of the richest sources of dietary flavonoids, mainly flavanols which is gaining importance in research since it has been proven to reduce the pathogenesis of diabetes and its complications [ 6 ]. Notably, our previous studies have demonstrated that cocoa supplementation improves the glucose metabolism in diabetic animals [ 7 ] and has beneficial effects on associated diabetic complications, mainly arterial stiffness [ 8 ] and nephropathy [ 9 ]. Several mechanisms have been described as being involved in these positive outcomes [ 10 ], including a possible prebiotic effect of cocoa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the factors mentioned above decrease the polyphenol content in cocoa and its derivatives, other studies have demonstrated that, even under these circumstances, with a low content of total polyphenols, they have a protective effect due to their functional property of antioxidant capacity [ 20 , 21 , 22 ]. In addition, food synergy may be responsible for the biological potential of cocoa derivatives, despite being subjected to chemical and physical transformations that cause said decrease in polyphenols [ 23 ].…”
Section: Introductionmentioning
confidence: 99%